The Model of Intellectual Capital based Information Technology and Its Implication on Employees Performance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research  focused on  higher of job rejection result and low of coordination among unit in problem solving of all the projects which is tend to decline of employees performance. The main issues discussed  in this reseach is factors influence it, namely human procurement ,development  and  intellectual capital based information technology.The research aims to analyze, describe and test the impact of   human procurement, development on intellectual capital and its implication on employees performance at  Indonesian Aerospace,Ltd. The research used was descriptive and explanatory survey method, so the research attempts to collect, present, analyze, and test hypotheses,  to make a consclusions were used  Structural Equation Model (SEM) approach. The design of  study is a survey reseach, the unit analysis selected were  core knowledge worker with a sample size of 303 from 1245 employees, based on Slovin’s formula. The results indicated  that human procurement, development have a simultaneously positive and significant effect on intellectual capital based information technology, and human procurement, development are either partialy or simultaneously have a positive and significant effect on employees performance level throught intellectual capital based information technology. The findings  are:(1) human procurement indicates low contribution on either  intellectual capital based information technology or employees performance, the highest score of human procurement dimension is selection and the lowest is recruitment dimension. 2) human development indicates low contribution on either intellectual capital or employees performance, the highest score of human development  dimension is education and the lowest is training dimension (3) intellectual capital based information technology  indicates moderate scores on employees performance level, the highest score of intellectual capital dimension is social capital  and the lowest is structure capital dimension. (4) the highest score size of employees performance dimension based on  employees perception  is goal and the lowest is motive dimension.